(untitled) (Bangladesh Journal of Dental Research & Education, 2013)
The objectives of this review were to examine the various methods of school oral health instruction process and to identify success factors for oral health promotion along with the development of a future framework of action for Oral Health Promotion. In this review, the members of the working groups performed the systematic literature search, screening process, rating of the evidence, assessment of the evidence and presentation of the contents of the evidence to the reader. In this study we performed literature searched published between1990 to 2013. Using database including MEDLINE, PUBMED, HINARI, Google and yahoo health. A total of 31 articles were retrieved and 15 of them were selected for review. Inclusion and exclusion criteria were chosen by working group such as studies reported any oral health promotion intervention in school were eligible for inclusion, Study conducted in the school for adult education or handicapped or disables were excluded, oral health education for adult were excluded In this review the working group tried to synthesize the qualitative and quantitative findings from the selected article. All studies were interventiona, the main intervention was oral health education in variable format along with other activities like fissure sealant, application of fluoride, distribution of tooth brush and toothpaste. In oral health education, presentation materials such as poster, tooth brushing model, life model and multimedia presentation were used. The investigators in five studies distributed tooth brush, tooth paste, tooth brushing calendar etc. Maximum investigators concluded that school oral health education is more or less effective in all situations, the summary of this review confirmed the hypothesis that there would be better and more homogenous oral health in schools where comprehensive oral health activities were developed compared with non-supportive schools. School oral health improvement activities has a great impact for the improvement of oral health among the children. The efficacy of oral health education is well-established and it was found that Oral health education in the school decreased the development of new dental diseases among school children. Majority of students had an adequate level of knowledge on oral health but low level of oral health practices. Reinforcement and encourage to maintain the oral health will be more effective for the long term sustainable oral health. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16613 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 45-50